The effect of rehabilitation exercises with body weight and rubber resistance on the range of motion and the strength of the sprained ankle muscles in female rugby players - Jawad, Baydaa; Yaseen, Ali; Ali, Shaima; Abdulhussein , Ahmed (Journal of Physical Education, 2024)
The study aimed to prepare a set of qualifying exercises to improve the muscular strength of the muscles surrounding the ankle joint by applying different resistances according to the nature of the movement of this joint, which is one of the second moving joints (flexion, extension and rotation of the right and left) in order to increase the efficiency of all muscles working on this joint according to those movements and identification On the impact of these exercises and assume that there will be statistical differences between the two tests of the research sample. The researcher used the semi-articulated experimental method with a pre- and post-test for one group. The injury was evaluated on the women's national team players during the season (2021-2022), who numbered (18) players, aged (18-20) years, body masses ranging from (51.5-72.5) kg, and lengths ranging (1.61-1.71) meters With an average of (1.68) meters, and the number of the final sample members reached (6) players, representing (33.3%) of the original research community. The following (arithmetic mean, standard deviation, T.test for correlated samples). The results of the study showed an improvement in the kinematic stretches and the strength of the ankle muscles on the various axes of the movement of the foot. He added, however, that the level of development of the strength of the ankle muscles was greater than the level of development of the kinetic stretches. The researcher recommended the necessity of applying the exercises that were used in the research in the case of an ankle sprain for its effectiveness in improving the functional duty of the foot, and conducting similar research and studies for the rest of the games and on the ankle joint, and special exercises should be prepared for the ankle muscles to avoid injury in the future.